2018
DOI: 10.1108/jarhe-03-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the career development and employability of information technology students

Abstract: Purpose The purpose of this paper is to understand the career development and employability needs of undergraduate information technology (IT) students at an Australian University, and their relation to students’ career interest. While many factors and stakeholders contribute to student career development, this study focused specifically on the student experience. Social cognitive career theory (SCCT) is used as an approach to understand the students’ needs of career development and employability. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Further as reported in McKenzie et al ( 2018 ) “of those who identified as coming to university from an alternative pathway, 30% reported TAFE as their highest level of education, with 21% reporting partial achievement of a university course as their highest level of education” (McKenzie et al, 2018 , p. 462). For IT students in regards to current employment status, “79% of students identified as not being employed in IT, yet 63% had an IT industry/network connection (knew someone who works in IT)” (McKenzie et al, 2018 , p. 462). In regards to who influenced students’ decisions to study IT at university, “65% reported ‘myself’ as the primary reason, with ‘a general interest’ as the second influence for studying IT” (McKenzie et al, 2018 , p. 462).…”
Section: Career Education In It At Deakin Universitymentioning
confidence: 88%
See 4 more Smart Citations
“…Further as reported in McKenzie et al ( 2018 ) “of those who identified as coming to university from an alternative pathway, 30% reported TAFE as their highest level of education, with 21% reporting partial achievement of a university course as their highest level of education” (McKenzie et al, 2018 , p. 462). For IT students in regards to current employment status, “79% of students identified as not being employed in IT, yet 63% had an IT industry/network connection (knew someone who works in IT)” (McKenzie et al, 2018 , p. 462). In regards to who influenced students’ decisions to study IT at university, “65% reported ‘myself’ as the primary reason, with ‘a general interest’ as the second influence for studying IT” (McKenzie et al, 2018 , p. 462).…”
Section: Career Education In It At Deakin Universitymentioning
confidence: 88%
“…Higher education institutions in Australia, such as Deakin University, are required to direct career development activities within the disciplines. As defined in McKenzie et al ( 2018 , p. 195) “career development learning can assist students to acquire knowledge, skills and attitudes that help them make better career choices and transitions”. Furthermore, career guidance can assist with the development of career management skills, enabling tertiary students to achieve the level of career maturity required.…”
Section: Career Education In It At Deakin Universitymentioning
confidence: 99%
See 3 more Smart Citations